Risk perception of sexually transmitted infections and HIV in Nigerian commercial sex workers living in Barcelona: a study protocol. Issue 7 (30th July 2013) - Coma Auli, Núria; Mejía-Lancheros, Cília; Berenguera, Anna; Mayans, Martí Vall; Lasagabaster, Maider Arando; Pujol-Ribera, Enriqueta
Abstract : Introduction: Sexually transmitted infections (STIs) and HIV are a serious global public health issue. These diseases are largely preventable, as they are directly and indirectly associated with potentially modifiable factors, including socioeconomic conditions. Sexual transmission is responsible for over 75% of new HIV infections worldwide. Moreover, commercial sex workers and their clients are two of the groups at the highest risk of acquiring and transmitting these infectious diseases, due to an extensive number of sexual encounters and the various factors related to commercial sex situations. This qualitative study aims to deepen the understanding of the risk perception of STIs and HIV and their associated factors in Nigerian commercial sex workers in the city of Barcelona. Methods and analysis: This is a qualitative, descriptive, interpretive study based on a social constructivist and phenomenological perspective conducted on a saturated sample of Nigerian commercial sex workers in the city of Barcelona. Data will be collected through semistructured individual and triangular group interviews. Information will be examined using a sociological discourse analysis, allowing us to understand the social and individual factors related to the risk perception of STIs and HIV in commercial sex workers. Discussion: Qualitative studies are an important element in identifying individual, social and contextual factors directly or indirectly related to the health/disease process. This qualitative study will provide essential knowledge to improve health promotion, prevention strategies and effective management of STIs both for commercial sex workers and their clients. Ethics: This study has been approved by the clinical research ethics committee (CEIC) of IDIAP Jordi Gol in Barcelona, 2012.